Translational Science in Vascular Aging: From Bench to Bedside—Insights from a VascAgeNet Roundtable - Elisabetta Bianchini; Lynn Roth; Pierre Boutouyrie; Smriti Badhwar; Achim Schwarz; Vincenzo Gemignani; Rosa Maria Bruno; Bernhard Hametner; Chloe Park; Giacomo Pucci; Ioana Mozos; Dimitrios Terentes-Printzios; et al. (Artery Research)
Abstract Translating vascular aging research from bench to bedside presents both significant opportunities and challenges. This paper summarizes insights from a roundtable discussion at the Artery 23 conference, featuring perspectives from basic science, clinical trials, regulation, and industry. The main conclusions of the discussion are as follows: basic science research must align with clinical relevance, using appropriate animal models and standardized measurement techniques. Pragmatic and registry-based clinical trials offer viable alternatives to traditional randomized controlled trials, facilitating real-world applicability. The regulatory landscape, particularly for software medical devices, must evolve to keep pace with technological advancements like artificial intelligence. Industry efforts focus on developing devices or solutions for vascular aging assessment and treatment strategies, yet face hurdles in large-scale adoption and reimbursement. Despite significant progress, the development of pharmacological interventions to mitigate vascular aging remains a critical need. This discussion underscores the importance of interdisciplinary collaboration to overcome barriers and translate scientific discoveries into clinical practice effectively.